Characteristics Factors In Health Workers Spread of Disease Prevention Occurrence of Hepatitis B - Irma H.Y Siregar; Ratnawati Hendari; Lanny Sunarjo (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2012)
Hepatitis B is one of contagious disease that can cause disaster. This disease is one of the targets of Millenium Development Goals (MDG's). This disease can be prevented by breaking down the chains of contacts from dentists or dental nurses. This research is descriptive with survey approach method. The samples are 30 respondents consist of dentists and dental nurses from 15 Puskesmas in Semarang residence. The instruments of this research are questioner and check lists. The data are analyzed by univariat and bivariat analyzes. The result of this research is that the characteristic factors influenced Hepatitis B are age, education, period of working, marriage status, additional work and supporting trainings. There are influence among attitude, period of working, marriage status and additional work toward the efforts of preventing the spread of Hepatitis B. On the other hand, there are no influence among knowledge and education toward the efforts of preventing the spread of Hepatitis B. It is recommended that the facilities of Puskesmas be upgraded and the training be held among dentists and dental nurses.